Measuring both primary and secondary outcomes when evaluating treatment effectiveness in alcohol and drug treatment programmes. (13th June 2018) - Patterson, Tess; Macleod, Emily; Hobbs, Linda; Egan, Richard; Cameron, Claire; Gross, Julien
Abstract : Background: The effectiveness of an alcohol or drug treatment program is frequently measured by changes in primary outcomes such as harmful substance use. It is also important to consider the impact of treatment on secondary outcomes focusing on the consequential harm of alcohol use, including poor health, impaired quality of life, interpersonal conflict and criminality. Here, we examine the effectiveness of a comprehensive alcohol and drug treatment intervention at producing real‐world change in both substance use and secondary consequential outcomes. Methods: A total of 325 participants attending a residential treatment service for harmful use of alcohol or drugs participated. The 12‐month prospective study measured outcomes at three time points: prior to treatment, at treatment‐end, and at a 3‐month follow‐up. A battery of psychometrically validated measures evaluated primary and secondary consequential outcomes. Results: At treatment‐end and at follow‐up, participants who completed a therapeutic dose of treatment demonstrated improvements not only in primary outcomes (i.e., reduced substance use) but also in a wide range of secondary outcomes measured, namely improvements in physical and mental health and quality of life, and decreases in criminal activity and negative consequences related to substance use and social problems. Conclusions: In evaluating treatment effectiveness, clinicians and researchers need to consider measuring consequential secondary outcomes in addition to primary outcomes related to substance use. Taken together, our findings demonstrate that a comprehensive alcohol and drug treatment program can produce real‐world positive change not only in substance use, but also in health, quality of life and reduced negative consequences of use.